First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China - Liu, Ming; Ren, Dong (Zootaxa, 2006)
In this paper a new species Cretonanophyes zherikhini sp. nov. and a new genus and species Abrocar brachyorhinos gen. et sp. nov., all placed within the family Eccoptarthridae, are described and illustrated. They pertain to the Late Jurassic Yixian Formation of the western Liaoning province, China. This finding represents the first record of fossil eccoptarthrids from China.